Kondisi dan Strategi Pertanian Indonesia dalam Memenangkan ACFTA (Asean-China Free Trade Area): Conditions and Strategies for Indonesian Agriculture in Winning the ACFTA (Asean-China Free Trade Area) - Rozci, Fatchur; Inti, Ristani Widya (Jurnal Ilmiah Manajemen Agribisnis, 2023)
This study intends to determine the condition of import and export, farmers' welfare, and food security in Indonesia in the face of ACFTA and to determine changes in the performance of the Indonesian agricultural sector after the ACFTA phenomenon. The research method used in this research is Literature Review to collect data and information about the state of agriculture in Indonesia, agricultural policies in Indonesia, Indonesia's export and import, and food security in Indonesia at the time the ACFTA was enacted. The results of this study indicate that in the implementation of the ACFTA, the Indonesian agricultural sector showed a decrease in production of 0.87% which resulted in a decrease in GDP of 0.22%. In addition, there is a possibility that Indonesia will become dependent on other countries' agricultural commodities, which could threaten the country's food security. Therefore, Indonesia has implemented several policies and strategies to overcome this, such as setting government purchasing prices and highest retail prices, developing food diversification, government agency supervision of local agricultural commodities, labeling, assessment and national standardization of local agricultural commodities. to provide incentives to farmers.